The compensatory reserve index predicts recurrent shock in patients with severe dengue - Trieu, HT; Khanh, LP; Ming, DKY; Quang, CH; Phan, TQ; Van, VCN; Deniz, E; Mulligan, J; Wills, BA; Moulton, S; Yacoub, S (BioMed Central, 2022)
Background Dengue shock syndrome (DSS) is one of the major clinical phenotypes of severe dengue. It is defined by significant plasma leak, leading to intravascular volume depletion and eventually cardiovascular collapse. The compensatory reserve Index (CRI) is a new physiological parameter, derived from feature analysis of the pulse arterial waveform that tracks real-time changes in central volume. We investigated the utility of CRI to predict recurrent shock in severe dengue patients admitted to the ICU.